Electrocatalyst performance at the gas/electrolyte interface under high mass transport conditions: optimization of the "floating electrode" method. - Lin,X; Zalitis,CM; Sharman,J; Kucernak,ARJ (ACS Applied Materials and Interfaces, 2020)
The thin-film rotating disk electrode (TF-RDE) is a well-developed, conventional ex-situ electrochemical method which is limited by poor mass transport in the dissolved phase and hence can only measure the kinetic response for Pt-based catalysts in a narrow overpotential range. Thus, the applicability of TF-RDE results in assessing how catalysts perform in fuel cells has been questioned. To address this problem, we use the floating electrode (FE) technique which can facilitate high mass transport to a catalyst layer composed of an ultra-low loading of catalyst (1-15 μgPt cmgeo-2) at the gas/electrolyte interface. In this paper, the aspects which have critical effects on the performance of the FE system are measured and parameterised. We find that in order to obtain reproducible results with high performance the following factors need to be taken into account: system cleanliness, break-in procedure, hydrophobic agent, ionomer type and the measurements of catalyst surface area and loading. For some of these parameters, we examined a range of different approaches/materials and determined the optimum configuration. We find that the gas permeability of the hydrophobic agent is an important factor for improving the hydrogen oxidation reaction (HOR) and oxygen reduction reaction (ORR) performance. We provide evidence that the suppression of the HOR and ORR introduced by the Nafion ionomers is more than a local mass transport barrier but that a mechanism involving the adsorption of the sulfonate on Pt also plays a significant role. The work provides intriguing insights into how to manufacture and optimize electrocatalyst systems which must function at the gas/electrolyte interface.